Prospects for the Development of the Present Stage of Higher School - I. I. Bobrova; E. G. Trofimov (Открытое образование (Москва), 2022)
The aim of the study was the situation around the future of higher education in Russia. It did not take shape yesterday, but recent events in the world prompted a decision to reform the existing system. Someone is satisfied with the current (nominally) Bologna system, while others are happy for the good old specialist programme. The authors decided to express their point of view on this problem, since they do not care what education system they work in.The authors examined the history of the development of Russian higher education: from monarchical to modern periods. Each one was evaluated. Positive and negative trends are identified in the higher education system. We compared the Bologna system with a specialist programme.Based on many years of teaching experience at the university; after analyzing the open publications of colleagues, we can say, “what should and should not be” in the new system.With the development of new information technologies, the range of information services is expanding, conditions are being created for the formation of a single global information and educational space. The attractiveness of the remote form is determined by the follow- ing principles: flexibility; modularity; economic efficiency; control automation; use of specialized technologies and teaching aids (video conferencing; test shells; chats; attendance check blocks; automated rating systems, etc.). The positive experience of the last ten years is the use of electronic educational complexes within the disciplines being read. Conclusion, leave electronic complexes in the assortment of the teacher. At the same time, it is necessary to remember the negative consequences for education of the use of distance technologies: lack of contact between the student and the lecturer; lack of control over the quality of acquired knowledge; security of transmitted information between students and educators; the need for a strong technical base for participants in the educational process and their level of preparedness when working with new systems and programmes.Zero testing of applicants showed their lack of logical thinking skills, fragmentary knowledge and lack of consistency. Definitely, it is necessary to abandon the Unified State Exam system when recruiting applicants.There is an acute problem with some specialties: there is an over- abundance of managers, accountants, lawyers. At the same time, there is a shortage, for example, of IT specialists and engineers. It is necessary to coordinate the list of specialties for the training of such specialists who will be in demand in 5-10 years.Over the past twenty years, the number of hours per teaching position has increased from 720 to 900 hours, which, naturally, has reduced the time (and desire) for science. It is necessary to revive the system of retraining of Faculty, ensuring the modification of knowledge and applied technologies in the learning process. It is necessary to raise the prestige of the teaching profession, its motivation.The specialist has confirmed its viability. It is only necessary to supplement it with technologies that have proven their effectiveness. The proposals made will be reflected in the organization of further work as a lecturer of higher education.